2018
DOI: 10.1101/275040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic modelling of quantitative proteome data predicts metabolic reprogramming of liver cancer

Abstract: Metabolic alterations can serve as targets for diagnosis and therapy of cancer. Due to the highly complex regulation of cellular metabolism, definite identification of metabolic pathway alterations remains challenging and requires sophisticated experimentation. Here, we applied a comprehensive kinetic model of the central carbon metabolism (CCM) to characterize metabolic reprogramming in murine liver cancer. We show that relative differences of protein abundances of metabolic enzymes obtained by mass spectrome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, we developed a novel approach that combines proteomic analysis of liver tissue with kinetic modeling of liver metabolism. In a preceding work [28], we demonstrated that this approach is capable of correctly predicting the metabolic phenotype of liver tumors in a mouse model. In this work, we used proteomics data on protein abundances in human HCC and the surrounding liver tissue to construct tumor‐specific metabolic models allowing us to monitor a larger panel of metabolites and fluxes in response to a typical plasma profile of metabolites and hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed a novel approach that combines proteomic analysis of liver tissue with kinetic modeling of liver metabolism. In a preceding work [28], we demonstrated that this approach is capable of correctly predicting the metabolic phenotype of liver tumors in a mouse model. In this work, we used proteomics data on protein abundances in human HCC and the surrounding liver tissue to construct tumor‐specific metabolic models allowing us to monitor a larger panel of metabolites and fluxes in response to a typical plasma profile of metabolites and hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were used between passages 10 and 25 at approximately 70-90% confluence. Primary murine hepatocytes were isolated from livers of wildtype (WT) and mTOR LEC mice at 8-12 weeks of age and maintained in DMEM with 10% FBS as previously reported [23]. Cells were cultured in a humidified incubator with 5% CO 2 at 37 C.…”
Section: Cell Lines and Primary Hepatocytesmentioning
confidence: 99%